2012
DOI: 10.1002/jsfa.5680
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity role of adzuki bean extract containing polyphenols: in vivo and in vitro effects

Abstract: The results of this study demonstrate that adzuki bean extract has high potential to serve as a natural anti-obesity agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 36 publications
4
46
1
Order By: Relevance
“…An adzuki bean extract suppressed obesity [7], reduced blood pressure [8], reduced the serum cholesterol level [9], suppressed hyperglycemia [10], and reduced the numbers of in ltrating macrophages and attenuated glomerular expansion in mouse and rat models of streptozoicin-induced diabetic nephropathy [11]. Flavonoids in the adzuki bean may mediate such bene cial e ects [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…An adzuki bean extract suppressed obesity [7], reduced blood pressure [8], reduced the serum cholesterol level [9], suppressed hyperglycemia [10], and reduced the numbers of in ltrating macrophages and attenuated glomerular expansion in mouse and rat models of streptozoicin-induced diabetic nephropathy [11]. Flavonoids in the adzuki bean may mediate such bene cial e ects [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…The assembled contig sequences reached to 450 Mb (83% of the genome) with an N50 of 38 kb, and the total scaffold sequences were 466. 7 Mb with an N50 of 1.29 Mb. Of them, 372.9 Mb of scaffold sequences were assigned to the 11 chromosomes of adzuki bean by using a single nucleotide polymorphism genetic map.…”
mentioning
confidence: 99%
“…Because adzuki bean contains rich amount of phenolic compounds and other bioactive compounds [6,7], it shows various physiological functions, such as anticancer, antioxidant, anti-obesity [13][14][15][16]. The edible fungi Monascus have been used to ferment rice, soybean, adlay, and dioscorea, and the previous studies reported that the fermentation of food materials by Monascus increases the contents of physiological active compounds, such as phenolic acids, γ-aminobutyric acid, free amino acids, isoflavone aglycones [38].…”
Section: Discussionmentioning
confidence: 99%
“…soybean and dioscorea) have also been fermented with Monascus, and the level of monacolin K and the antioxidant capacities were highly increased [11,12]. However, despite reports on the health benefits of adzuki bean [13][14][15][16], the effects of fermentation by Monascus on adzuki bean have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%